What Makes Cirrhosis Irreversible?—Consideration on Structural Changes - Dezső, Katalin; Paku, Sándor; Kóbori, László; Thorgeirsson, Snorri S.; Nagy, Péter (Frontiers in Medicine, 2022)
Several studies have shown that liver fibrosis, and even cirrhosis can be reversed, disproving the old "dogma" that cirrhosis is irreversible. In addition to scaring, vascular alterations appear to be critically important in the progression of chronic liver diseases. To overcome the 'tipping-point' of cirrhosis, we need to understand in depth what might make it irreversible in some cases. Morphologically, the initial, as well as the advanced stages of cirrhosis are characterized by specific structural changes. The hallmark of the initial stage is the division of the original liver parenchyma by centro-central or porto-portal septa. No significant vascular changes are observed in this stage. The advanced stage is characterized by several morphological alterations: (i) The main feature is the parenchymal extinction, with intact portal vein branches, hepatic artery branches, and biliary ductules; (ii) In the extinct areas we observed numerous loops in the ductular network, indicating the disruption of the hepato-biliary junctions; (iii) Although the ductular progenitor cells are able to generate hepatocytes via the budding process, the newly formed hepatocyte nodules cannot re-establish the original lobular architecture due to their disorganized growth. In conclusion, this regenerative process characteristic for the advanced stage, contributes to circulatory disorders, perpetuates parenchymal injury and may lead to the irreversibility of cirrhosis.